"Does ERAS benefit higher BMI patients? A single institutional review". Issue 3 (March 2021) - Shin, Hope D.; Rodriguez, Abigail M.; Abraham, Jasson T.; Cargile, John C.; Brown, Candace N.; Altman, Andrew M.; Saint-Cyr, Michel H.
Summary: Background: Enhanced recovery after surgery (ERAS) is increasingly used in plastic surgery to optimize patient care. Mitigating the risk of postoperative complications is particularly important in patients with risk factors, such as obesity. The objective of this study is to evaluate the impact of the ERAS pathway in patients, stratified by BMI, undergoing free flap breast reconstruction on length of stay and complications. Methods: A retrospective review of all patients who underwent abdominally based free flap breast reconstruction from January 2014 to December 2017 was performed. Data collected include participation in the ERAS protocol, patient demographics, length of stay (LOS), complications (minor and major), and 30-day reoperation rates. Results: A total of 123 patients met the inclusion criteria, with 36 non-ERAS and 87 ERAS patients. ERAS patients had a shorter length of stay than non-ERAS patients (4.14 vs. 4.69, p = 0.049). Higher BMI patients progressively benefited from their involvement in an ERAS pathway: class I obese patients had an LOS decrease of 0.99 days ( p = 0.048) and class II+ obese patients had an LOS decrease of 1.35 days ( p = 0.093). Minor complications, major complications, and reoperation rates were similar between ERAS and non-ERAS patients ( p >0.05). Conclusion: Utilization of an ERAS protocol for free flap breast reconstruction safely decreases LOS, especially with increasing BMI. Patients benefit from an ERAS protocol without increasing risk of postoperative complications, compared to non-ERAS patients of similar BMIs.